2006
DOI: 10.1021/jo0609834
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Diastereofacial Selectivity in Hydride Reductions of N-tert-Butanesulfinyl Imines

Abstract: A variety of N-tert-butanesulfinyl imines were reduced with NaBH4 in THF containing 2% water to provide the corresponding secondary sulfinamides in high yield and diastereoselectivity. By using the same sulfinyl imine starting materials and changing the reductant to L-Selectride, the stereoselectivity could be efficiently reversed to afford the opposite product diastereomer in high yield and selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
108
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(111 citation statements)
references
References 22 publications
3
108
0
Order By: Relevance
“…[21][22][23] A recent report has shown that 12 can be produced as a mixture with other phenolic monomers through bimetallic hydrogenolysis of organosolv lignin in water.…”
Section: Technologiestoproducechemicalsandfuelsfromrenewablementioning
confidence: 99%
“…[21][22][23] A recent report has shown that 12 can be produced as a mixture with other phenolic monomers through bimetallic hydrogenolysis of organosolv lignin in water.…”
Section: Technologiestoproducechemicalsandfuelsfromrenewablementioning
confidence: 99%
“…Entries 11-20 in Table 1 show that the phenyl substituent on the imino group of 1b notably decreases the reactivity of the substrate in the Cu(I)-mediated catalytic b-boration reaction. The average enantioselectivity also significantly decreases, however, we were particularly delighted to see that one of the most accessible chiral ligands, the monodentate phosphoramidite L9, promotes the formation of 2b in quantitative yield and with 95% ee (Table 1, entry 19).…”
Section: Resultsmentioning
confidence: 99%
“…Faul and co-workers highlighted the influence of the solvent on syn:anti-diastereoisomer ratios in the reduction of sulfinamides using NaBH 4 . [19] Inspired by these examples, we also carried out reductions of 2a with NaBH 4 in wet THF (2% H 2 O) and MeOH. While NaBH 4 in wet THF produced similar results to those obtained with NaBH 4 in EtOH (Table 2, entry 3), the reduction in MeOH gave the anti-diastereoisomer with high selectivity (Table 2, entry 4).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the N-aryl imine 6, the main and value starting, can be prepared from commercially available 3-indolaldehyde 4 and 2-cyanoaniline 5, according to published methods (Colyer et al, 2006). This aldimine is obtained as a white and stable solid after purification by recrystallization in 95 % yield (Fig.…”
Section: Synthesis and Purification Of The New The (3-indolmethyl)acementioning
confidence: 99%